2014
DOI: 10.7314/apjcp.2014.15.11.4493
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Epidermal Growth Factor Receptor Mutations between Primary Tumors and Lymph Nodes in Non-small Cell Lung Cancer: a Review and Meta-analysis of Published Data

Abstract: Background: Epidermal growth factor receptor (EGFR) mutations in non-small cell lung cancer (NSCLC) can predict the clinical response to tyrosine kinase inhibitor (TKI) therapy. However, EGFR mutations may be different in primary tumors (PT) and metastatic lymph nodes (MLN). The aim of this study was to compare EGFR mutations between PT and the corresponding MLN in NSCLC patients, and provide some guidelines for clinical treatment using TKI therapy. Materials and Methods: A systematic review and meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…. The majority of previous studies demonstrated that the overall concordance rate of EGFR mutation status was about 87.8% between primary tumor and paired metastatic lymph nodes . A higher concordance rate was observed in Sun et al .…”
Section: Discussionmentioning
confidence: 79%
“…. The majority of previous studies demonstrated that the overall concordance rate of EGFR mutation status was about 87.8% between primary tumor and paired metastatic lymph nodes . A higher concordance rate was observed in Sun et al .…”
Section: Discussionmentioning
confidence: 79%
“…However, depending on patient ability and/or willingness to undergo sampling, whether samples are available or evaluable, and differing diagnostic practices between countries [ 12 , 13 , 21 – 25 ], either the primary tumour or a metastatic lesion may be biopsied [ 26 ]. However, the concordance in mutation status between matched primary and metastatic tumours is the subject of debate [ 3 , 27 33 ], with limited understanding as to whether discordance reflects actual heterogeneity in mutations, or is an artifact of technical/sensitivity limitations in testing methodology [ 34 43 ]. Nevertheless, given that the collection of multiple invasive samples from a patient with NSCLC is undesirable, it is important to ascertain whether the mutation status of an individual patient’s NSCLC can be accurately characterised from biopsies of either the primary or metastatic sites.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment predictive molecular tests are usually performed on the primary tumor (T). Although the first studies correlating genetic alterations in metastatic lymph nodes have been deluding (36)(37)(38), other reports demonstrated that primary tumor mutational status not always correlate with the metastatic lymph node genetic status (39). Chen et al showed that the therapeutic response to tyrosine kinase inhibitor (TKI) acting on EGFR is more pronounced in patients with mutated tumor in the metastatic foci (40): therefore the mutational status of the N component could be more predictive of therapy response than that of the primary tumor (41).…”
Section: Discussionmentioning
confidence: 99%